Activism - Dias Ramos, Afonso; Snow, Tom (Whitechapel Gallery, 2023)
Activism is a critical point of contention for institutions and genealogies of contemporary art around the world. Yet artists have consistently engaged in activist discourse, lending their skills to social movements, and regularly participating in civil and social rights campaigns while also boycotting cultural institutions and exerting significant pressure on them. This timely volume, edited by Tom Snow and Afonso Ramos, addresses an extraordinary moment in debates over the institutional frameworks and networks of art including large-scale direct actions, as well as a radical rethinking of art venues and urban spaces according to racial, class, or gender-based disparities, including demonstrations against the extractive and exploitative practices of neoliberal accumulation and climate catastrophe. From ACT UP and its affiliate groups since the dawn of the AIDS crisis to the counter-spectacle and street theatrics of the so-called Arab Spring and Occupy, to ongoing protest movements such as Black Lives Matter, Rhodes Must Fall, and Decolonize This Place, activist aesthetics has proven increasingly difficult to define under traditional classifications. Resurgent campaigns for decolonial reckoning, ecological justice, gender equality, indigenous rights and antiracist pedagogies indicate that the role of activism in contemporary art practice urges a critical reassessment. One pressing question is whether contemporary art's most radical politics now takes place outside, against, or in spite of, conventional sites of display such as museums, biennials, and galleries
Literaturverzeichnis Seite 231-236
Artists surveyed include: ACT UP, Basel Abbas & Ruanne Abou-Rahme, Allora & Calzadilla, Tania Bruguera, Black Audio Film Collective, Chto Delat, Andrea Fraser, Nan Goldin, Sanja Iveković, Gulf Labor, Amar Kanwar, Leslie Labowitz, Liberate Tate, Sethembile Msezane, Zanele Muholi, Jan Nikolai Nelles & Nora Al-Badri, Decolonize This Place, Michael Rakowitz, Oliver Ressler
Writers include: Dave Beech, Judith Butler, Amílcar Cabral, Elias Canetti, Douglas Crimp, Jodi Dean, Gilles Deleuze, T.J. Demos, Nina Dubrovsky, Süreyyya Evren, Catherine Flood, Matthew Fuller, David Graeber, Gavin Grindon Félix Guattari, Brian Holmes, Carrie Lambert-Beatty, Lucy Lippard, Yates McKee, MTL Collective, Gregory Sholette, Françoise Vergès, Peter Weiss, Eyal Weizman
Keywords: Geschichte 1970-2023; Politics in art; Art and social action; Art and social conflict; Politique dans l'art; Art et action sociale; Art et conflits sociaux; Aktivismus; Engagierte Kunst; Politische Kunst; Aufsatzsammlung